Letter to Jane Tolmach from Stephen Reinhardt - Stephen Reinhardt:::::: (1972)
In this March 13, 1972 letter, Stephen Reinhardt congratulates Jane Tolmach on her selection as a member of the Muskie Delegation. He expresses confidence that Senator Muskie can win the California primary through strong volunteer organizing efforts and emphasizes the importance of district-by-district campaign work. Reinhardt also provides information about the upcoming Democratic National Convention in Miami, including dates and logistical details, and encourages continued work toward victory.